Pre-melhoramento em capsicum: identificação de espécies, hibridação interespecífica e variabilidade genética em caracteres de sementes - (:unkn) unknown (Universidade Federal do Amazonas, 2015)
This research aimed to evaluate the potential of near infrared spectroscopy (NIR) to distinguish species of the genus Capsicum, evaluate the availability of cross between subsamples of Capsicum chinense Jacq. with Capsicum annuum L. and analyze the genetic variability from genetic parameters for the characters: germination and vigor of seed germplasm of C. chinense Jacq.. To study the discrimination of Capsicum species with near infrared spectroscopy (NIR) analyzing 53 hits 4 species, and analyzed by spectrophotometer and whole dried leaves. Six spectral readings were collected per sample. The data matrix used in the analysis consisted of 500 variables (spectral bands) for the species. The results showed the variables (spectral bands) allowed the separation of four groups based on their spectral signatures and the estimated distances have identified the species C. chinense Jacq. as the most divergent demonstrating that it was possible to distinguish species of Capsicum genus using spectroscopy technique Leaf Near Infrared. For the study of interspecific hybridization were crossed thirty subsamples of C. chinense Jacq., Used as male parents and a commercial variety harsh bark Ikeda (C. annuum L.), female parent. The results showed that obtaining viable seeds and fruits in interspecific cross was possible, but the results vary according to use the subsamples. To study the estimation of genetic parameters of seed germination characters in C. chinense Jacq. 30 subsamples peppers were used in two experiments in the laboratory of seeds at the Faculty of Agricultural Sciences, Federal University of Amazonas. The following characteristics were analyzed: germination percentage at 07 days, germination percentage at 14 days, GSI (Germination Speed Index), ATG (Average Time of Germination) and SW (Seed Weight). The results showed that the subsamples showed high genetic variability for seed germination characteristics possible to estimate the variability of the genotypes of C. chinense Jacq. through the vigor and germination and depending on the morphotype, you can select individuals through higher seed germination characteristics.
Keywords: Infravermelho próximo; Cruzamento interespecífico; Capsicum; Near infrared; Interspecific crossing; CIÊNCIAS AGRÁRIAS: AGRONOMIA